Championing Culturally Responsive Leadership for Evaluation Practice. Issue 143 (September 2014) - Aponte‐Soto, Lisa; Ling Grant, Deborah S.; Carter‐Johnson, Frances; Colomer, Soria E.; Campbell, Johnavae E.; Anderson, Karen G.
Abstract: The Graduate Education Diversity Internship (GEDI) program empowers students of color to become adaptive leaders, change agents, partners, and facilitators through exposure to theory, experiential training, leadership development, and mentorship in order to advance culturally responsive evaluation (CRE) practices that respond to context and community values in a respectful and positive manner (Nelson‐Barber, LaFrance, Trumbull, & Aburto, 2005 ). A case study of the first six GEDI cohorts was conducted to evaluate the program's impact on CRE leadership development. This chapter validates how GEDI transformative leadership strategies can be applied by any profession to champion CRE practitioners and promote a society that values social justice, equity, and democratic change.